PWM Control Scheme for Quasi-Switched-Boost Inverter to Improve Modulation Index - Khawaja, Fuad Munther Fuad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The typical two stage power inverters, a boost DC – DC converter is utilized to make a constant DC bus voltage. Then a DC – AC inverter (H- Bridge) is used to invert the DC voltage to AC voltage but in this type both of the power switches in the leg of the H – bridge cannot be turned on at the same time because it makes a short circuit and thus may damage the device. Shoot-through protection is a way used to prevent and solve this problem by controlling the shoot through state in a single phase stage quasi-switched boost inverter (qSBI). However, it has different methods, the most common is the simple boost control (SBC). This thesis presents a new pulse width modulation (PWM) control scheme to improve the modulation index for the qSBI. In this thesis, a circuit is designed with 400W and 110V and 50 HZ output. The related circuits and the operating principles were analyzed using Matlab/Simulink. The analysis simulation results proved that the control scheme can enlarge the modulation index, reduce the voltage stress on the capacitor, diode and switches, as well as reduce the frequency of the inductor current, ripples of the capacitor voltage, lowering the shoot through current. Keywords: Pulse-Width Modulation (PWM), quasi-Z-Source Inverter (qZSI), quasi-Switched-Boost Inverter (qSBI), shoot-through, Simple Boost Control (SBC).

ÖZ: İki katmanlı güç evirgeçlerinde DA giriş gerilimi genellikle yükseltici bir DA-DA çevirgeçle elde edilir. Bunun ardından, H-köprüden oluşan bir DA-AA evirgeç kullanılarak DA gerilim AA gerilime dönüştürülür. Fakat bu tür sistemlerde, H-köprünün bir bacağındaki güç anahtarları, kısa devreye yol açıp anahtarlara zarar verebileceği için, aynı anda kapatılamazlar. Bu tür kısa devre vuruşlarına karşı koruma, tek faz yarı-anahtarlamalı yükseltici çevirgeçlerde (qSBI) kısa devre oluşumunu denetim altına alarak gerçekleştirilir. Basit yükseltici denetimi yönteminin en yaygın olduğu bu tür korumanın bir çok çeşidi vardır. Bu tez, son zamanlarda yayınlanmış ve yarı-anahtarlamalı yükseltici çevirgeçlerde kipleme endeksini iyileştiren yeni bir darbe genişliği kipleme denetim yöntemini içeren yeni bir çalışmayı ele almaktadır. Bu çalışmada, 400 W çıkış gücü, 50 Hz 110 V çıkış gerilimine sahip bir devre çözümlenip benzetimleri yapılmıştır. İlgili devrelerin çalışma ilkeleri de Matlab/Simulink kullanılarak incelenmiştir. Bu çözümleme ve benzetim sonuçları, yeni yöntemin kipleme endeksini genişlettiğini, sığa, diyot ve anahtarlar üzerindeki gerilim baskısını azalttığını, bobbin akımının sıklığını azalttığını, ve kısa devre akımını da düşürdüğünü göstermiştir. Anahtar kelimeler: Darbe Genişliği Kipleme, Yarı-Z-Kaynak- Çevirgeç, Yarı-anahtarlamalı Yükseltici Çevirgeç, Kısa Devre Vuruşu, Basit Yükseltme Denetimi.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2019. Supervisor: Prof. Dr. Osman Kükrer.
Keywords: Electrical and Electronic Engineering; Electric power systems--PWM power converters; Electric current converters; Voltage-frequency converters; Pulse-Width Modulation (PWM); quasi-Z-Source Inverter (qZSI); quasi-Switched-Boost Inverter (qSBI); shoot-through; Simple Boost Control (SBC)